Drug-therapy-related problems and pharmacist interventions in the medical ward in northeast Ethiopia: focus on types, acceptability, and impacts - Endalifer, Bedilu Linger; Ayta, Yared Dergu; Tsigie, Abate Wondesen; Wondmkun, Yehualashet Teshome; Kassa, Mekuanint Terefe; Amare, Gedefaw Getnet; Ejigu, Yenesew Wudu; Derseh, Manaye Tamrie; Ambaye, Abyou Seyfu (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to identify drug-therapy-related problems, possible interventions, acceptability, and impacts of the interventions among patients admitted to the medical ward.MethodsA hospital-based prospective interventional study was conducted in Hakim Gizaw Hospital, Debre Berhan City, Ethiopia. The sample size for the study was determined using a single proportion formula and 183 participants were recruited accordingly. Data were collected by two clinical pharmacists using a predesigned tool. The drug-therapy-related problems, interventions, and acceptability of the interventions were categorized on the basis of the Pharmaceutical Care Network Europe V.9.1 tool. The impacts of the interventions were then assessed using the clinical, economic, and organizational multidimensional tool. The data were analyzed using SPSS version 26 software.ResultDrug-therapy-related problems were identified in 27.3% of the patients, with an average incidence of 2.36 ± 0.76 events per patient. The treatment-effectiveness-related problems accounted for half (60/121) of these drug-related problems, followed by drug-selection-related causes (31/121, 26.3%), dose selection (19/121, 16.1%), and other undefined but related causes (19/121, 16.1%). A total of 143 interventions were delivered by the clinical pharmacists, of which those discussed with the prescriber (55, 38.4%) were the most frequent type. Approximately three-fourths (106/143) of these interventions were accepted. Among the pharmacist interventions, 36.4% had minor, 8.4% had major, and 4.9% showed negative clinical impacts. Economically speaking, 48.2% of the interventions were found to reduce treatment costs; organizationally, approximately 28.7% of the interventions had improved the quality of care while 14.0% had worsened it. The duration of hospitalization, comorbidities, and admission locations were observed to significantly influence the drug-related problems.ConclusionThere was a high prevalence of drug-therapy-related problems as well as high acceptance rate of interventions in the medical ward, which were found to have pronounced economic, clinical, and organizational impacts.